Монгол заргын бичиг: Судалгааны арга зүй, аргачлалын асуудал - Ч. Тамир; Д. Төрдалай (Acta Mongolica, 2005)
This work is the research about Mongolian petition related with the XIX-XX century. Petition is not only considerable but related document which doesn’t have from other research sources. It’s different because the petition shows Mongolian ordinary civil life, honesty, intellegence, and social problems without any filter, and if gives us the opportunaty to research and study tradition, culture of formal letter, the abuse of authority and law and social problems and its conflict. It raises some issues about methodology and method how to study petition with sociological new aspects of history further.